Analisis Sikap Petani Melon Terhadap Atribut Pupuk NPK 161616 di Desa Klotok Menggunakan Metode Multiatribut Fishbein - Fauziah, Diana Maharani; Rizkiyah, Noor; Fitriana, Nisa Hafi Idhoh (Universitas Galuh, 2025)
This study aims to analyze the attitudes of melon farmers in Klotok Village toward the attributes of NPK 161616 fertilizer using the Multi-Attribute Fishbein method. Melon is a horticultural commodity with significant potential in Tuban Regency, a major melon producer in East Java. The research method involved 40 melon farmers as respondents, the data collected was questionnaires and observations. The results indicate that farmers have a positive attitude toward the fertilizer attributes, particularly in terms of brand and price. The brand attribute received the highest attitude score, followed by price, indicating that these two factors significantly influence farmers' purchasing decisions. Additionally, the legality and product information attributes also received considerable attention. This study recommends that fertilizer producers enhance information transparency and strengthen their brand to increase farmers' trust.